2008
DOI: 10.1518/001872008x312350.
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Perceptions of Risk and Anxiety and Pilot Involvement in Hazardous Events

Abstract: Pilots may be involved in risk-taking behavior because they perceive less risk in, and are implicitly less afraid of, hazardous conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
1
15
1
1
Order By: Relevance
“…Unfortunately, the majority of analyses have been one-sided in that only pilots involved in accidents have been studied (Hunter et al, 2011;Li et al, 2001;McFadden, 1996;Platenius & Wilde, 1989;Wong et al, 2006). In some cases, pilot judgment or actions in simulated conditions, either via simulation or survey, have been evaluated (Drinkwater & Molesworth, 2010;O'Hare et al, 2006;Pauley, O'Hare, Mullen, & Wiggins, 2008;Wiggins, Hunter, O'Hare, & Martinussen, 2012). However, little inquiry into the differences between individuals who have been involved in accidents has been compared to those who have not (Hunter, 2001;Urban, 1984).…”
Section: Overview Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the majority of analyses have been one-sided in that only pilots involved in accidents have been studied (Hunter et al, 2011;Li et al, 2001;McFadden, 1996;Platenius & Wilde, 1989;Wong et al, 2006). In some cases, pilot judgment or actions in simulated conditions, either via simulation or survey, have been evaluated (Drinkwater & Molesworth, 2010;O'Hare et al, 2006;Pauley, O'Hare, Mullen, & Wiggins, 2008;Wiggins, Hunter, O'Hare, & Martinussen, 2012). However, little inquiry into the differences between individuals who have been involved in accidents has been compared to those who have not (Hunter, 2001;Urban, 1984).…”
Section: Overview Of the Studymentioning
confidence: 99%
“…Female pilots were found to significantly differ from males in terms of flight time when involved in pilot error events, as females have lower experience levels (p , 0.001). Pauley et al (2008) investigated differences in pilot attributes of participants in risk and anxiety assessments related to hazardous events. Inter-correlations evaluated using the Hazardous Events Scale (HES) and the Implicit Association Test (IAT).…”
Section: Studies Of Pilot Attributes Associated With Accident Factorsmentioning
confidence: 99%
“…Specifically, the IAT was constructed in order to record participants' implicit associations between depictions of high injury probability (HIP) scenarios and low injury probability (LIP) scenarios and sets of words meaning risky (danger, threatened, harm, lethal, and hazard) and safe (protected, secure, home, reliable, and sure). These words were the same as those used by Pauley et al (2008). Ten colour images, five showing HIP scenarios and five showing LIP scenarios, were also used.…”
Section: Materials and Apparatusmentioning
confidence: 99%
“…Wiegmann, Goh, & O'Hare, 2002). In many risk situations, including the aviation example above, the associated risks are widely known and therefore one or more of these individual difference variables, paired with changes in attitudes and feelings towards the risk, will be the most likely predictors (see Pauley, O'Hare, Mullen, & Wiggins, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have tried to understand the factors which play into a pilot's decision to fly into adverse weather or continue into poor visibility conditions. Reviews of aviation crash reports and studies with private and commercial pilots in simulators have identified several hypotheses, including poor situational awareness where the pilot does not adequately perceive that he/she is flying into adverse weather [Goh and Wiegmann, 2002; Wiegmann et al, 2002], overconfidence in abilities, or inaccuracy in risk perception [Goh and Wiegmann, 2002; Wiegmann et al, 2002; Coyne et al, 2008; Pauley et al, 2008], and social pressure by passengers [Goh and Wiegmann, 2002], by company management, or self‐induced [Shappell and Wiegmann, 2003; Bearman et al, 2009].…”
Section: Introductionmentioning
confidence: 99%